The Role of Entrepreneurship Literacy in Community Empowerment to Improve Local Economic Potential in Denai Sarang Burung Village - Ritha F Dalimunthe; Meutia Nauly; Nor Hafizah; Fadli; Ramadani (Neo Journal of economy and social humanities, 2025)
This study aims to examine the role of entrepreneurial literacy in community empowerment to enhance local economic potential in Denai Sarang Burung Village. The methods used include digitalization training, strengthening market access, and collaboration with international partners. The results show that improving entrepreneurial literacy significantly increases the capacity and competitiveness of women MSME actors. The establishment of institutions such as the Merah Putih Cooperative strengthens coordination and collective marketing, supporting business sustainability. The challenges of women's dual roles as housewives and entrepreneurs have begun to be identified and are the focus of sustainable solutions. This study provides an important foundation for the development of an inclusive and sustainable community-based local economy.